STRATEGI KEPEMIMPINAN DALAM MENINGKATKAN LOYALITAS PENDIDIK DAN TENAGA KEPENDIDIKAN DI MADRASAH IBTIDAIYYAH: KAJIAN STUDI LITERATUR - Nur Fahmuddin Hanif; Ziddan Arrauf; Bambang Sri Anggoro; Sovia Mas Ayu (EDUCATIONAL : Jurnal Inovasi Pendidikan & Pengajaran, 2026)
ABSTRACT Teacher and educational staff loyalty is a crucial factor in sustaining the quality of education in Madrasah Ibtidaiyyah. However, previous studies have predominantly focused on improving teacher performance rather than synthesizing leadership strategies of madrasah principals to foster the loyalty of all educational human resources. This study aims to analyze effective madrasah principal leadership strategies for enhancing the loyalty of teachers and educational staff through a literature review approach. The study employed a descriptive qualitative method by examining scholarly articles published in reputable national and international journals between 2022 and 2026, retrieved from Google Scholar and other academic databases. The data were analyzed using the content analysis technique, involving the stages of identification, selection, data reduction, categorization of findings, interpretation, and conclusion drawing. The findings indicate that the most consistently effective leadership strategies for enhancing loyalty include transformational, participative, humanistic, and spiritual leadership, supported by open communication, continuous professional development, and appropriate recognition. Teacher and educational staff loyalty is influenced by leadership practices, the work environment, employee welfare, interpersonal relationships, and the religious culture developed within the madrasah. The study concludes that integrating leadership strategies oriented toward human resource development and the reinforcement of Islamic values represents the most relevant approach to strengthening loyalty while sustainably improving the quality of education in Madrasah Ibtidaiyyah. ABSTRAK Loyalitas pendidik dan tenaga kependidikan merupakan salah satu faktor penting dalam menjaga keberlanjutan mutu pendidikan di Madrasah Ibtidaiyyah. Namun, berbagai penelitian sebelumnya lebih banyak menitikberatkan pada peningkatan kinerja guru dibandingkan sintesis mengenai strategi kepemimpinan kepala madrasah dalam membangun loyalitas seluruh sumber daya manusia pendidikan. Penelitian ini bertujuan menganalisis strategi kepemimpinan kepala madrasah yang efektif dalam meningkatkan loyalitas pendidik dan tenaga kependidikan melalui pendekatan studi literatur. Penelitian menggunakan metode kualitatif deskriptif dengan menelaah berbagai artikel ilmiah dari jurnal nasional dan internasional bereputasi yang diterbitkan pada periode 2022–2026 dan diperoleh melalui Google Scholar serta pangkalan data ilmiah lainnya. Data dianalisis menggunakan teknik content analysis melalui tahapan identifikasi, seleksi, reduksi, pengelompokan temuan, interpretasi, dan penarikan simpulan. Hasil kajian menunjukkan bahwa strategi kepemimpinan yang paling konsisten meningkatkan loyalitas meliputi kepemimpinan transformasional, partisipatif, humanis, dan spiritual yang didukung komunikasi terbuka, pembinaan profesional berkelanjutan, serta pemberian penghargaan yang proporsional. Loyalitas pendidik dan tenaga kependidikan dipengaruhi oleh kepemimpinan, lingkungan kerja, kesejahteraan, hubungan interpersonal, dan budaya religius yang berkembang di madrasah. Penelitian ini menyimpulkan bahwa integrasi strategi kepemimpinan yang berorientasi pada pengembangan sumber daya manusia dan penguatan nilai-nilai Islam menjadi pendekatan yang paling relevan untuk memperkuat loyalitas sekaligus mendukung peningkatan mutu Madrasah Ibtidaiyyah secara berkelanjutan.